2016
DOI: 10.5194/acp-16-8375-2016
|View full text |Cite
|
Sign up to set email alerts
|

The incorporation of an organic soil layer in the Noah-MP land surface model and its evaluation over a boreal aspen forest

Abstract: Abstract. A thick top layer of organic matter is a dominant feature in boreal forests and can impact land-atmosphere interactions. In this study, the multi-parameterization version of the Noah land surface model (Noah-MP) was used to investigate the impact of incorporating a forest-floor organic soil layer on the simulated surface energy and water cycle components at the BERMS Old Aspen site (OAS) field station in central Saskatchewan, Canada. Compared to a simulation without an organic soil parameterization (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Due to the low thermal conductivity, soil organic matter generally prevents heat into the soil column (Fisher et al, 2016; Koven et al, 2009). Consistent with the study of Gao et al (2015) and Chen et al (2016), the cooling effect of SOM (Lawrence & Slater, 2008) results in a lower ST and delayed thawing process in this study, especially that of deep soils (Figures 3 and 4, Table 4). The inability of LSMs to accurately simulate the soil moisture of the QTP has been widely reported (Chen et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Due to the low thermal conductivity, soil organic matter generally prevents heat into the soil column (Fisher et al, 2016; Koven et al, 2009). Consistent with the study of Gao et al (2015) and Chen et al (2016), the cooling effect of SOM (Lawrence & Slater, 2008) results in a lower ST and delayed thawing process in this study, especially that of deep soils (Figures 3 and 4, Table 4). The inability of LSMs to accurately simulate the soil moisture of the QTP has been widely reported (Chen et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Yetemen, Ireson, Barr, Melton, and Black () demonstrated the overestimation of ET at the OJP site applying coupled Canadian Land Surface Schemes and Canadian Terrestrial Ecosystem Model (CLASS‐CTEM; V. Arora, ). L. Chen et al () applied NOAH‐MP to the OA site and found that ET was overestimated in the spring and underestimated in the summer, except during drought conditions, when it was slightly overestimated. They also found the simulations were improved by including an organic soil layer in the model.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple options are available for surface water infiltration and runoff, and groundwater transfer and storage including water table depth to an unconfined aquifer. Recent evaluation efforts showed that Noah‐MP improves the simulation of land‐surface water and heat exchange over different underlying surfaces such as snowpack, frozen soil, grassland, and forest (Barlage et al, ; Chen et al, , ; Gao et al, ; Yang et al, ) and demonstrated the utility of Noah‐MP in assessing land surface modeling uncertainties (Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The new Noah-MP LSM uses multiple options for key land-atmosphere interaction processes to improve major Noah weaknesses in representing the seasonal and annual cycle of snow, hydrology, and vegetation . Unlike the Noah bulk surface treatment, Noah-MP contains a distinct vegetation canopy layer defined by a canopy top and bottom, crown radius, and leaves, with prescribed dimensions, orientation, density, and radiometric properties that allow (Barlage et al, 2015;Chen et al, 2014Chen et al, , 2016Gao et al, 2015;Yang et al, 2011) and demonstrated the utility of Noah-MP in assessing land surface modeling uncertainties (Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%